Ethno-linguistic patterns of degree completion in BC universities: How important are high-school academic achievement and institution of entry? - Sweet, Robert; Pullman, Ashley; Adamuti-Trache, Maria; Robson, Karen (Canadian Journal of Higher Education, 2019)
We examine bachelor's degree completion in the British Columbia post-secondary system, which is noted for its multiple pathways to graduation and ethnically diverse student population. Employing an administrative longitudinal dataset, we compare how the probability of degree completion by students enrolled at research-intensive, teaching-intensive, and college-technical institutions differs by ethno-linguistic background and high school grades. Estimates from multi-level logistic regression models demonstrate that Korean, Tagalog, and Vietnamese speakers have lower probabilities of degree completion than English-speaking students. The type of institution a student initially enters is, however, an important correlate of degree completion for all ethno-linguistic groups. Students with lower high school grades who initially enter a research-intensive institution are more likely to graduate compared with higher-achieving students who enter a teaching-intensive or college-technical institution. To improve completion by institutional type and among ethno-linguistic groups, our study highlights the need for research on why degree completion is lower at certain institutions for all ethno-linguistic groups and consistently lower among Korean, Tagalog, and Vietnamese speakers regardless of their level of academic achievement in high school or the type of post-secondary institution they initially entered.